Aktivitas Antibakteri Ekstrak Etanol Daun Cengkeh (Syzygium aromaticum (L.) Merr. & Perry) Terhadap Bakteri Escherichia coli - Siti Khoiriyah; Andi Pradana; Indah Kurniawati (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Escherichia coli is a bacteria that causes diarrhea transmitted through water or food contamination and is treated with antibiotics. Excessive antibiotics have the potential to cause resistance. Natural ingredients such as clove leaves are used as an alternative to overcome resistance because they have antibacterial activity. This study aims to determine the antibacterial activity of clove leaf extract (Syzygium aromaticum (L.) Merr. & Perry) against Escherichia coli bacteria and its minimum inhibitory level. Clove leaves were macerated using 96% ethanol. Identification of eugenol content was carried out using thin layer chromatography. The antibacterial activity test in this study used the well diffusion method with concentrations of 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%. In this study, the results of clove leaf extract extraction were obtained with a yield of 15.7975%. The results of identification using thin layer chromatography showed that clove leaf extract contains eugenol. Ethanol extract of clove leaves has antibacterial activity against E. coli bacteria at concentrations of 5%, 6%, 7%, 8%, 9% and 10%, while at concentrations of 1% to 4% it has no antibacterial activity.